2009
DOI: 10.1021/la9023426
|View full text |Cite
|
Sign up to set email alerts
|

Low Viscosity Highly Concentrated Injectable Nonaqueous Suspensions of Lysozyme Microparticles

Abstract: Subcutaneous injection of concentrated protein and peptide solutions, in the range of 100–400 mg/mL, is often not possible with a 25- to 27-gauge needle, as the viscosity can be well above 50 cP. Apparent viscosities below this limit are reported for suspensions of milled lysozyme microparticles up to nearly 400 mg/mL in benzyl benzoate or benzyl benzoate mixtures with safflower oils through a syringe with a 25- to 27-gauge needle at room temperature. These apparent viscosities were confirmed using a cone-and-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…A standard curve using known solutions with various viscosities provided a linear correlation between the time to draw 50 μl from the conical vial to the viscosity with an r 2 value greater than 0.99 18 . These results are consistent with previous work with suspensions of model proteins and protein solutions which found that the time to draw up a specified amount of the sample in a syringe was correlated linearly to viscosity 15,18,22 .…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…A standard curve using known solutions with various viscosities provided a linear correlation between the time to draw 50 μl from the conical vial to the viscosity with an r 2 value greater than 0.99 18 . These results are consistent with previous work with suspensions of model proteins and protein solutions which found that the time to draw up a specified amount of the sample in a syringe was correlated linearly to viscosity 15,18,22 .…”
Section: Methodssupporting
confidence: 92%
“…This viscosity measurement was previously characterized for subcutaneous injections of highly concentrated solutions of monoclonal antibodies 15 and non-aqueous suspensions of lyosyzme 22 . Due to our very small sample volumes (~100 ul), we were concerned that evaporation would rapidly affect values measured with a traditional viscometer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hundreds of protein therapeutics are currently in clinical use or advanced human trials due to their lower toxicity and more predictable and selective behavior in vivo compared to small-molecule drugs (Adama and Weiner, 2005;Danni et al, 2007;Frokjaer and Otzen, 2005;Miller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…All of the electrostatic phenomena occurring in presence of electrolyte solutions stems from the electric double layers (EDLs) formed near a charged surface, and the properties of the EDL are known to be critical concern in various applications [19][20][21][22][23][24][25], such as floatation, colloid systems, microfluidics, biological systems, and biomedical engineering. A quantitative understanding of the EDL is necessary to predict the influence of various control parameters on the occurrence of these phenomena, and the PB theory has been the core in EDL analysis to describe the electric potential and ion distributions near charged surfaces immersed in electrolyte solutions.…”
Section: Introductionmentioning
confidence: 99%